Determining the Citizen Loyalty Factor of COVID-19 Website Using the Trust Model - Azty Acbarrifha Nour; Lukito Edi Nugroho; Paulus Insap Santosa (IJITEE (International Journal of Information Technology and Electrical Engineering), 2021)
One of the information technology (IT) utilization by the government is the establishment of an official website for public access, designed to disseminate information about the COVID-19. Gaining public trust in the information dissemination is getting harder due to the amount of information, while the government is striving to provide reliable information. The service quality provided on the official website will affect the public’s trust and desire to use these services. Citizen loyalty is known when people intensively use the government electronic services because they believe in the government and its e-services based on perceived satisfaction and service quality. This research studied the effect of service quality, trust, and user satisfaction on user loyalty when using e-services by the Special Region of Yogyakarta (DIY) government. The study used a trust model developed by Alkraiji and Ameen and applied it to the official COVID-19 website. Data were collected from 100 respondents in the DIY who were in the productive age range. The experiment was carried out using explanatory and inferential techniques with multiple linear regression methods. The results of the study indicate that all model hypotheses are accepted. The relationship between antecedents and citizen loyalty was more influenced by trust in government and e-government. This finding explains why Yogyakarta citizen trust the government and its electronic services and will be loyal to use these services during the COVID-19 pandemic, as well as other facilities in the future.